Penicillium Brevicompactum causing bulb rot on Hippeastrum × Hybridum in Argentina - Quiroga, Gisela Alejandra Ramona (2017)
In July 2015, bulbs of Hippeastrum × hybridum imported for cultivation in Buenos Aires (Argentina) showed loss of firmness, rot and green mold. Small pieces from the edge of the lesions were surface disinfected with 2% sodium hypochlorite for 90 s, rinsed in sterilized distilled water and incubated on potato dextrose agar at 22°C. Isolates of Penicillium brevicompactum Dierckx (Samson and Frisvad, 2004) were consistently obtained, and one of them coded INTA-IF-502 was chosen to confirm pathogenicity. Healthy, unwounded and needle-punctured bulbs were immersed for 1 min in suspensions of 1.4 × 106 conidia ml-1, while those immersed in sterilized water served as controls. The bulbs were individually planted in pots filled with a sterile soil/perlite mixture (80/20), and enclosed in polyethylene bags for the first three days. All the plants from inoculated bulbs showed yellowish foliage and loss of turgidity in 45 days. Ten days after, the plants from inoculated punctured bulbs had died and those from inoculated unwounded bulbs showed an advanced wilt. Rotten bulbs and roots, and green mold were observed on inoculated plants eased out of the pots whereas controls remained healthy. The pathogen was successfully recovered from infected organs and deposited in La Plata Spegazzini Collection as LPSC1146. The morphological identification (Visagie et al., 2014) was confirmed by DNA sequence data of the β-tubulin gene (GenBank accession No. KY216143) showing 99% identity to accession AY674437 (type of P. brevicompactum CBS 257.29). This finding represents the first record of P. brevicompactum associated with bulb rot of Hippeastrum × hybridum in Argentina.